Key concepts of medical physiology - Chatterjee, Amar (UiTM, 2011)
physiology is about how cell are kept alive and how their environment is maintained so that the integrity of the cells is preserved. Human body start from a single cell and contains about 100 trillion cells at maturity. Cell need an uninterrupted supply of energy to maintain their form and function. Cell remain surrounded by extracellular fluid a medium through which exchange betwen cell and the external environment accour.